Eco-Theology–Based Deep Learning as a Paradigm for Environmentally Conscious Islamic Religious Education Learning - Jumaah Jumaah; Saparudin Saparudin; Nuruddin Nuruddin (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
The The escalating global environmental crisis—reflected in climate change, ecological degradation, and declining environmental awareness—poses serious challenges for educational institutions, including Islamic Religious Education. This study examines the integration of eco-theology–based deep learning as a transformative pedagogical paradigm for cultivating environmental consciousness within Islamic Religious Education. The primary issue addressed is the limited integration of ecological values in prevailing instructional practices, which tend to prioritize cognitive achievement while insufficiently fostering ethical awareness and practical responsibility toward environmental stewardship. This research employs a qualitative descriptive approach through systematic literature review and conceptual analysis of educational theories, Islamic teachings, and eco-theological perspectives. The study formulates an integrative instructional framework that synthesizes deep learning principles such as critical inquiry, reflective engagement, collaborative learning, and experiential activities with Islamic environmental ethics grounded in the concepts of khilāfah, amānah, mīzān, avoidance of fasād, and wasatiyyah. The findings indicate that eco-theology–based deep learning promotes holistic student development encompassing cognitive understanding, affective awareness, and behavioral commitment to environmental care. Learners develop an enhanced perception of their role as khalīfah (stewards of the Earth), integrating spiritual consciousness, moral responsibility, and ecological literacy within real-life practices. The study concludes that eco-theology–based deep learning offers a viable and transformative model for reorienting Islamic Religious Education toward sustainability, character formation, and active engagement in addressing contemporary environmental challenges